Factors that Affect Mother to the Children (2-36 month) Exclusion in Sub PIN Diphtheria - Swardana, Nicholas Fransida; Wahjuni, Chatarina Umbul (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTSub National Immunization Week (PIN) Diphtheria is an additional immunization activity simultaneously in 19 regencies/ cities as an attempt to cope with outbreak of diphtheria in East Java. Sub PIN Diphtheria coverage result in 2012 in the Sukolilo Village, Surabaya in children(2â36 months) did not fulfill the target because there are many children(2â36 months) that did not participate. This study was conducted to analyze the factors that affect mother to the children(2â36 months) exclusion in Sub PIN Diphtheria in the Sukolilo Village, Surabaya 2013, include: maternal age, maternal education level, maternal employment, number of children, motherâs level of knowledge, maternal attitudes, husband support, community support, and exposure information. This study conducted with observational analytic approach and case control design. Large sample of 90 mothers drawn by simple random sampling. Statistical analysis is used multiple logistic regression with Î± < 0.05. The results showed that the variables that affect the exclusion of mothers to immunize children(2â36 months) in Sub PIN Diphtheria sequentially are less maternal attitude (p = 0.000), maternal less knowledge (p = 0.005), the husband does not support (p = 0.047), and were not informed (p = 0.018). Whereas maternal age, maternal education level, maternal employment, number of children, and the community support has no effect because the p value < 0.05. Therefore it is necessary counseling and motivation to the mother, socialization to the husband, and optimize health promotion media in order to minimize the exclusion Sub PIN Diphtheria future.Keywords: children (2â36 months), diphteria, immunization, knowledge, Â Â Â Â Â Â Â Â Â Â Â Â attitude